Factors influencing glycocalyx degradation: a narrative review - Wang, Jing; Ma, Lan; Fang, Yu; Ye, Tengteng; Li, Hongbo; Lan, Peng (Frontiers in Immunology, 2025)
The glycocalyx is a layer of villus-like structure covering the luminal surface of vascular endothelial cells. Damage to the glycocalyx has been proven linked to the development of many diseases. However, the factors that promote damage to the glycocalyx are not fully elaborated. This review summarizes factors leading to the reduction of the glycocalyx in detail, including inflammatory factors, ischemia-reperfusion, oxidative stress, lipids, glucose, high sodium, female sex hormones and others. Additionally, the mechanisms underlying its degradation are discussed. To better prevent and treat related diseases induced by glycocalyx degradation, it is a meaningful measure to avoid these factors.